The Role Of Strategic Planning In Improving The Quality Of Tax Awareness: Field Study At The General Tax Authority - Alaa Yahya Younis Saeed (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research seeks to identify strategic tax planning, its importance and its impact on improving the quality of taxpayers’ tax awareness, and since this research is in the General Tax Authority, strategic tax planning is an explanatory variable that affects the improvement of taxpayers’ tax awareness as a responsive variable, and the main goal is To research prove the importance of adopting strategic planning in the field of taxes in increasing taxpayers’ awareness, also identifying the nature of the impact of strategic tax planning on the taxpayer and increasing his awareness when targeting it, as the theoretical aspect dealt with an introduction to strategic tax planning and tax awareness, while the practical analytical aspect is Complementary and complementary to the theoretical aspect through a questionnaire distributed to the sample members and then transcribed and analyzed. The most important findings reached by the researcher were that the General Authority for Taxes lacks the presence of a division or even a unit related to strategic planning to develop plans and work to monitor implementation, while setting standards for this purpose. But more important Recommendations: It was necessary to update tax legislation to suit the requirements of the market economy and support the mechanisms of strategic planning.